Collection and analysis of human trafficking news from Brazilian websites - Nascimento, Ana Rosa A.; Rigato, Matheus; Santos, João V. L. P. dos; Neres de Sousa, João V. C.; Traina Jr., Caetano; Cazzolato, Mirela T. (Anais Estendidos do Simpósio Brasileiro de Banco de Dados (SBBD); 2026: Anais Estendidos do XLI Simpósio Brasileiro de Bancos de DadosDO - 10.5753/sbbd_estendido.2026.249585, 2026)
Human trafficking (HT) is a serious crime, yet structured datasets on the topic remain scarce in Brazil. This paper presents a dataset of 3,556 news articles mentioning HT, collected from three Brazilian online portals. We describe a Python-based pipeline for collecting data from heterogeneous websites and discuss the main challenges encountered during extraction. The corpus was analyzed using AI-assisted labeling, semantic similarity, dimensionality reduction, clustering, and supervised classification. The dataset and collection methodology aim to support future research on HT, natural language processing, open data analysis, and public safety in the Brazilian context.